Education Policies for Upward Social Mobility in Latin America - Daude, Christian (OECD Development Centre Policy Insights, 2010)
Income is very unequally distributed in Latin America - but so too are opportunities for upward mobility. Early childhood development is a powerful mechanism to level the social playing field. More and better secondary education is key. Better administration of schools, combining greater flexibility with more accountability, a modern system of evaluation and incentives for school administrators and teachers are important ingredients for reforms